PERANCANGAN MEDIA PEMBELAJARAN AUTOCAD BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) PADA MATA PELAJARAN PRODUKTIF TEKNIK GAMBAR BANGUNAN DALAM BENTUK CAKRAM OPTIK - Fajri Hatta; Adhi Purnomo; Arris Maulana (Jurnal Pensil : Pendidikan Teknik Sipil, 2012)
The design of this innovative work does in order to enhance to quality of learning for the students and create some variations in learning especially in studying AutoCAD. The implementation time of designing this work starts from December 1st, 2011 until December 31st, 2011.Designing this innovative work engages seven steps. Those are observation, compilation of material, compilation of information path, data compilation, initial elaboration, evaluation, and final elaboration. Evaluation steps are implemented in two phases of validation and revision. The first validation phase is media validation done by themedia expert from the Learning Centre – State University of Jakarta (Pusat Sumber Belajar – PSB UNJ). The second validation is the substantial and instructional validation which is executed by two teachers of AutoCAD in SMKN Jakarta.The results of validation show that the design of the media reaches the marvelous qualification level based on the validation from the media expert which gives the point 4.49 in the scale of 5, and based on the validation of substantial and instructional which shows the result of 4,23 in the scale of 5. From the review, we can summarize that this learning media is analyzed as a good and development needed for the institution needed around this country.